2011
DOI: 10.3109/01913123.2010.544843
|View full text |Cite
|
Sign up to set email alerts
|

CD44+/CD24Cells Are Transit Progenitors and Do Not Determine the Molecular Subtypes and Clinical Parameters in Breast Carcinomas

Abstract: CD44(+)/CD24(-) cells have been associated with breast cancer stem/progenitor cell features. However, the status of this phenotype cells in normal, benign and malignant breast tissues has not been studied, and the clinical correlation of this subpopulation in breast cancer is not fully understood. The present study sought to identify these cells in a series of normal, benign, and malignant breast tissues and explore their correlation to the molecular subtypes of breast carcinoma and conventional pathological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“… 8 10 However, other studies showed that CD24 is not a cancer stem cell marker. 11 , 12 , 14 For example, Xu et al 14 found that both A549 and H560 CD24 + cells did not show enhanced tumor-forming ability than CD24 − cells. In this study, using the soft agar assay, we demonstrated that the CD24 + subpopulation has self-renewal properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 10 However, other studies showed that CD24 is not a cancer stem cell marker. 11 , 12 , 14 For example, Xu et al 14 found that both A549 and H560 CD24 + cells did not show enhanced tumor-forming ability than CD24 − cells. In this study, using the soft agar assay, we demonstrated that the CD24 + subpopulation has self-renewal properties.…”
Section: Discussionmentioning
confidence: 99%
“… 10 However, other studies showed that lack of CD24 expression appears to be critical for the identification of the breast cancer stem-like cells (CSCs). 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…breast tumor progression or patient survival (13,14). Further studies demonstrated that the CD44 + /CD24 -/low cells were transit progenitors; however, they did not determine either the molecular subtype or clinical parameters in breast cancer (15).…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, CD44 is indicated to be a promising biomarker for diagnosis 92 and prognosis. 93 , 94 …”
Section: Clinical Significance Of Cd44mentioning
confidence: 99%